Influence of glycerol concentration on survival of entomopathogenic nematodes through cryopreservation - Chau, Nguyen Ngoc; Ehlers, Ralf-Udo (Academia Journal of Biology, 2014)
A modified procedure based on reduced concentration of glycerol for cryopreservation of infective juvenile stage nematodes has been developed using indigenous isolates Steinernema and Heterorhabditis collected from Vietnam. The survival of infective juveniles (IJs) depended on some factors such as concentration of glycerol, IJs concentration and timing for thawing. Optimum survival for both genera was archived with 12,000 IJs/ml in glycerol and 7,500 IJs/ml in ringer’s solution. For Steinernema strains optimum survival also was observed with 12,000 IJs/ml in 10% glycerol concentration whereas with the same IJs concentration in 7.5% Glycerol concentration. The maximum retentions of Steinernem were 45.9-95% whereas these retentions of Heterorhabditis isolates were 81.5-95.2%. The survival of Vietnamese epn isolates in post-cryopreservation was more or less low that only 4 Steinernema isolates among 26 treated were survival whereas only 3 per 12 Heterorhabditis isolates were post-cryopreservation survival. Among survival isolates, apart from two isolates S-TG10 and S-TX1 with survival percentage was lower as 5 and 45.9%, respectively, remaining isolates with survival percentage was higher as 70-95%. For toxicology, Steinernema were 78-87 retention of original virulence to GM larvae, whereas this toxicology of Heterorhabditis was 76-83.5 retention of original virulence to GM larvae.